2018
DOI: 10.1073/pnas.1720433115
|View full text |Cite
|
Sign up to set email alerts
|

Broadening horizons: Sample diversity and socioecological theory are essential to the future of psychological science

Abstract: The present lack of sample diversity and ecological theory in psychological science fundamentally limits generalizability and obstructs scientific progress. A focus on the role of socioecology in shaping the evolution of morphology, physiology, and behavior has not yet been widely applied toward psychology. To date, evolutionary approaches to psychology have focused more on finding universals than explaining variability. However, contrasts between small-scale, kin-based rural subsistence societies and large-sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
69
1
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 90 publications
(72 citation statements)
references
References 87 publications
(83 reference statements)
0
69
1
2
Order By: Relevance
“…In addition, niche diversity potentially offers a consilient way in which to think about disparate descriptors of societal complexity. For example, Gurven [62] recently showed that higher national-level personality trait covariation is also associated with greater cultural tightness [63], lower individualism [64], and lower gender egalitarianism [65], all of which may reflect stricter constraints limiting the availability of diverse socioecological niches to individuals within those societies.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, niche diversity potentially offers a consilient way in which to think about disparate descriptors of societal complexity. For example, Gurven [62] recently showed that higher national-level personality trait covariation is also associated with greater cultural tightness [63], lower individualism [64], and lower gender egalitarianism [65], all of which may reflect stricter constraints limiting the availability of diverse socioecological niches to individuals within those societies.…”
Section: Discussionmentioning
confidence: 99%
“…However, we were able to collect data from the vast majority of Bondongo parents and children who were present in the village at the time of the research project (Boyette et al, ). We argue that this limitation is offset by the advantage of collecting data in these environments, which are tremendously underrepresented in existing research on family function as well as children's development, biology, and health (Gurven, ; Henrich et al, ).…”
Section: Limitationsmentioning
confidence: 98%
“…While research on aging and the epigenome has expanded to a number of different global settings and populations, it remains the case that the vast majority of studies on epigenetic age acceleration (EAA) focus on adult populations in societies such as the U.S., Europe, and other similar settings (Horvath et al, ; Ryan et al, ). Specifically, those societies are industrialized and wealthy (at the national level) and feature ecologies in which energetic stress is largely absent and pathogen stress is low (Gurven, ; Henrich, Heine, & Norenzayan, ). Those socioecological conditions differ substantially from those experienced by much of the global population, particularly in low‐resource or impoverished settings with minimal access to clinical, biomedical care (Gurven, ; Lozano et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fink et al [1] report that Maasai men and women rated strong walkers as both weaker and less attractive than weak walkers: a surprising reversal of the effects found in previous research [2,3]. These data from a non-WEIRD population are highly valuable for assessing the universality gait perception [4]. However, the conducted analyses relied on participants' ratings of attractiveness and strength that were averaged across groups of stimuli (i.e.…”
mentioning
confidence: 99%